Optimization of underground open intermediary space comfort in TOD complexes: A case study of Chongqing, China - Lili, Dong; Yufeng, He; Xiang, Chen; Na, Cheng; Tao, Liu (Frontiers in Public Health, 2023)
High-quality transit-oriented development (TOD) complexes can alleviate numerous problems arising from rapid urbanisation, representing an important trend toward urban sustainability. However, existing TOD complexes are facing various problems. Underground open intermediary spaces can be introduced to optimise them. In this study, we classified these spaces into four types. The static Taguchi method was used to simulate their physical environment generated by some impact factors. Numerical simulation results show that space shape is a primary influencing factor for the luminous and thermal environments, the window-atrium ratio (W/A ratio), and hole-atrium ratio (H/A ratio) are contradictory factors between the luminous and thermal environments of these spaces, profile inclination angle, and sunken plaza height are primary impact factors for the acoustic environment, and skylight type has a low weight of influence on the physical environment. Their luminous and acoustic environment comfort can be averagely improved by 200%, and thermal environment comfort by 21%, but the potential for optimising the thermal environment comfort of their shallow space (underground space depth ≤ 10 m) is relatively low. Subsequently, we discussed the necessity of comfort optimisation as the passive optimisation design of underground open intermediary space’s physical environment in TOD complexes in the future.